Navegación fluvial e ingeniería militar en España, siglos XVI-XVII. De Pérez de Oliva y Antonelli, a Leonardo Torriani y Luis Carduchi - Suárez Quevedo, Diego (Anales de Historia del Arte, 2007)
Really it would be paper’s engineering, because in practice only been accoplished a minimal, but we have in this documents importants testimonies of artitic culture in the Spain of Habsburg, and the fundamental works of the engineers of his service, from the reasoning of Pérez de Oliva and his civil humanism. The hard counterpoint really was the war’s art.